2020
DOI: 10.1142/s0218127420502442
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Behaviors of a Delayed Prey–Predator Model with Beddington–DeAngelis Functional Response: Stability and Periodicity

Abstract: This work investigates a prey–predator model with Beddington–DeAngelis functional response and discrete time delay in both theoretical and numerical ways. Firstly, we incorporate into the system a discrete time delay between the capture of the prey by the predator and its conversion to predator biomass. Moreover, by taking the delay as a bifurcation parameter, we analyze the stability of the positive equilibrium in the delayed system. We analytically prove that the local Hopf bifurcation critical values are ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…As the conditions in Case 4 are satisfied, this leads to existence of 𝜔 ± . The corresponding values of critical time delays are given from expression (18). As mentioned in Lemma 4.1, the sum of multiplicities of roots in C + will change only when a root appears on or crosses the imaginary axis.…”
Section: A Finite K Number Of Instability Switching Occurs Whenevermentioning
confidence: 99%
See 1 more Smart Citation
“…As the conditions in Case 4 are satisfied, this leads to existence of 𝜔 ± . The corresponding values of critical time delays are given from expression (18). As mentioned in Lemma 4.1, the sum of multiplicities of roots in C + will change only when a root appears on or crosses the imaginary axis.…”
Section: A Finite K Number Of Instability Switching Occurs Whenevermentioning
confidence: 99%
“…Similar conclusion was derived by Rabago and Collera 17 in their delayed intraguild predator‐prey model. Zhang et al 18 have considered a predator‐prey model where time delay is due to the gestation of predator. They found that periodic solutions are possible when time delay is varied, i.e., predator coexists with the prey in an oscillatory mode.…”
Section: Introductionmentioning
confidence: 99%